Prevalence of sarcopenia in Asian older adults: A comparison of nine diagnostic criteria across different regions - Wei-Cheng Chiu; Tung-Wei Kao; Tao-Chun Peng (Experimental Gerontology)
Objective: This study aimed to compare sarcopenia prevalence in older adults using nine diagnostic criteria from different regions to assess how these guidelines influence prevalence rates within the same population. Additionally, we analyzed variations across subgroups to identify factors contributing to prevalence differences. Methods: A total of 1760 participants aged 65–99 were enrolled. Bioelectrical impedance analysis was used to assess muscle mass, while muscle strength and physical performance were evaluated using grip strength, gait speed, and the repeated chair stands test. Sarcopenia prevalence was determined based on definitions provided by ESPEN (European Society for Clinical Nutrition and Metabolism), EWGSOP (European Working Group on Sarcopenia in Older People), IWGS (International Working Group on Sarcopenia), SCWD (Society for Sarcopenia, Cachexia, and Wasting Disorders), AWGS (Asian Working Group for Sarcopenia), FNIH (Foundation for the National Institutes of Health), and SDOC (Sarcopenia Definitions and Outcomes Consortium). Additionally, prevalence rates were assessed across subgroups based on age, sex, and BMI categories. Results: Sarcopenia prevalence varied from 4.8 % (n = 79), based on the FNIH criteria, to 16.1 % (n = 261), according to the EWGSOP criteria. Among females, higher prevalence rates were observed using the ESPEN, AWGS, and EWGSOP2 criteria, while the FNIH criteria indicated a higher prevalence in males. Prevalence increased with age, especially in those aged 85 and older. Lower BMI was associated with higher sarcopenia prevalence according to most criteria, except the FNIH and ESPEN. Conclusion: The notable variability in sarcopenia prevalence across different diagnostic criteria highlights the need for population-specific guidelines. Refining diagnostic criteria to address demographic variations could enhance the accuracy and applicability of sarcopenia assessments. Future studies should aim to further tailor diagnostic approaches and interventions to meet the needs of diverse populations.